Формалізація задачі прийняття рішень для вибору оптимальної структури гібридної енергетичної системи - Шулима, Ольга Василівна; Шендрик, Віра Вікторівна; Давідсон, Пол (НТУ "ХПІ", 2016)
Розглядається модель прямої агрегації оціночних критеріїв в задачі багатокритеріального аналізу альтернативних варіантів побудови енергетичних мереж з відновлювальними джерелами енергії. Для розрахунку загальної функції корисності пропонується процедура приведення кількісних і якісних критеріїв до "нечіткості". За схемою Беллмана-Заде розглядається ранжування альтернативних рішень вибору структури енергетичної системи в межах трьох сценаріїв. При умові неявної переваги альтернативи пропонується оцінка альтернатив за максимінним критерієм. Результати досліджень можуть бути використані у відповідній системі підтримки прийняття рішень.

The paper is considering a problem of providing energy via Hybrid Renewable Energy Systems. It is proposed a model of direct evaluation of aggre-gated criteria and a model of ranking alternatives in multicriteria analysis of building energy grid with renewable energy sources. A systematic multicriteria decision analysis technique is described for alternative selection and bid evaluation based on utility theory and which permits different types of criterias to beevaluated. To do it is proposed to use the scheme Bellman-Zadeh and ranking alternatives within different scenarios: socio-economic and energy-efficient. To calculate the total utility function proposed procedure to bring quantitative and qualitative criteria to the "fuzziness". If results show implicit benefits then offered toevaluate alternatives by maximin criterion. A Ukraine case study is used to illustrate the technique. The theoretical basis and the advantages of the technique are also presented. The research results can be used in the appropriate decision support system.
The formalization of decision-making problem to select the optimal structure of a hybrid energy system
Keywords: енергетична система; відновлювальні джерела енергії; альтернативи; схема Беллмана-Заде; багатокритеріальна задача; energy system; renewable energy sources; alternatives; multicriteria decision making problem; scheme Bellman-Zadeh